2003
DOI: 10.1099/jmm.0.05072-0
|View full text |Cite
|
Sign up to set email alerts
|

Medium pH-dependent redistribution of the urease of Helicobacter pylori

Abstract: Helicobacter pylori is an aetiological agent of gastric disease. Although the role of urease in gastric colonization of H. pylori has been shown, it remains unclear as to where urease is located in this bacterial cell. The purpose of this study was to define the urease-associated apparatus in the H. pylori cytoplasm. H. pylori was incubated at both a neutral and an acidic pH in the presence or absence of urea and examined by double indirect immunoelectron microscopy. The density of gold particles for UreA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 19 publications
1
47
0
2
Order By: Relevance
“…Immunoelectron microscopy showed an acid-and UreI-dependent reorganization of UreA and UreB from a predominately cytoplasmic location to the membrane, and native PAGE identified a UreA-UreB-UreI membrane complex (13,40). In the current study, using Western blot analysis, it was found that the transition from a neutral pH to an acidic pH for 30 min resulted in a ϳ2-fold increase in the levels of UreA and UreB at the membrane in the wild-type organism.…”
Section: Discussionmentioning
confidence: 89%
“…Immunoelectron microscopy showed an acid-and UreI-dependent reorganization of UreA and UreB from a predominately cytoplasmic location to the membrane, and native PAGE identified a UreA-UreB-UreI membrane complex (13,40). In the current study, using Western blot analysis, it was found that the transition from a neutral pH to an acidic pH for 30 min resulted in a ϳ2-fold increase in the levels of UreA and UreB at the membrane in the wild-type organism.…”
Section: Discussionmentioning
confidence: 89%
“…It can be envisioned that the small proportion of activated urease is sequestered in a compartment of the cell to improve its activity in connection for instance with the ammonium-incorporating enzyme, glutamine synthetase, under conditions of normal growth or with the urea inner membrane channel, UreI, for efficient substrate delivery upon acid stress. Accordingly a UreI-dependent membrane association of urease was reported previously (47,61).…”
Section: Table I Tap-tagged Proteinsmentioning
confidence: 99%
“…The proton-gated urea channel UreI regulates the rate of the urea entry into the cytoplasm and is required for acid survival and gastric infection (151,205,237). When UreI is activated by an acidic pH of the medium, urease moves from the inner portion to the outer portion of H. pylori, closer to the source of urea, so presumably ammonia production occurs at or near the inner membrane (110). In H. felis, a second urease system, UreA2B2, has been detected (180), but its function and regulation are currently unknown.…”
Section: Virulence Factors Of Gastric Non-h Pylori Helicobacter Speciesmentioning
confidence: 99%